Answer:
The simplification for the expression is given as =( 7 + 2(a-3))/(a-3)
Step-by-step explanation:
To simplify the expression we will first convert the words to values in numbers and alphabets.
StartFraction 5 Over a minus 3 EndFraction minus 4 divided by 2 + StartFraction 1 Over a minus 3 EndFraction
= 5/(a-3) -4/2 + 2/(a-3)
Having done that, let's move on and simplify the expression.
5/(a-3) -4/2 + 2/(a-3)
= 5/(a-3) -2+ 2/(a-3)
= 5/(a-3) + 2/(a-3) -2
= 7/(a-3) -2
=( 7 + 2(a-3))/(a-3)
Answer:
y=5x+31
Plot points at: (-4,11), (-6,1), (-3, 16)
Step-by-step explanation:
y-1=5(x+6)
y-1=5x+30
y=5x+31
Answer:
i think you had written the formula wrongly
so if it was -30x not -30
Step-by-step explanation:
x intercept when y=0
-30x = 15
x= -0.5
y intercept when x=0
5y= 15
y=3
- if this is the one you want
-30 +5y=15
5y =45
y=9
and there not x intercept { }